2021
DOI: 10.1680/jgeot.19.p.350
|View full text |Cite
|
Sign up to set email alerts
|

Flume study on the effects of microbial induced calcium carbonate precipitation (MICP) on the erosional behaviour of fine sand

Abstract: DisclaimerThe AM is yet to be copyedited and formatted in journal house style but can still be read and referenced by quoting its unique reference number, the digital object identifier (DOI). Once the AM has been typeset, an 'uncorrected proof' PDF will replace the 'accepted manuscript' PDF. These formatted articles may still be corrected by the authors. During the Production process, errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal relate to these ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 37 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…One of the recent studies by Clarà Saracho et al . 27 investigated the influence of tangential erosion by utilizing erosion function apparatus (EFA) and reported that treatment of soil sample with one pore volume of 0.08 M biocementation solution for 10 days brought erosion values down to a negligible level for a tangential flow of 0 to 0.185 m/s 27 . To the authors’ best knowledge, no study for riverbank erosion mitigation with a bio-stimulation approach has been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…One of the recent studies by Clarà Saracho et al . 27 investigated the influence of tangential erosion by utilizing erosion function apparatus (EFA) and reported that treatment of soil sample with one pore volume of 0.08 M biocementation solution for 10 days brought erosion values down to a negligible level for a tangential flow of 0 to 0.185 m/s 27 . To the authors’ best knowledge, no study for riverbank erosion mitigation with a bio-stimulation approach has been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were saturated and then the ow velocity was increased stepwise at intervals of a 5-minute time interval (Supplementary data, gure 3). This stepwise incremental ow methodology was considered based on the study by Clarà Saracho et al 35 , as the critical ow velocity is expected to increase with the biocementation treatment levels. The ow was operated using the control panel and velocity was measured on three different points near the sample using a pulse velocity meter.…”
Section: Erodibility Test For a Bed Slope In Hydraulic Umementioning
confidence: 99%
“…Later, Jiang et al 34 investigated rainfall-induced erosion simulations for various treated soil 0.2,1 and 2.0 M by spraying of cementation solution four times and observed that 0.2 and 1.0 Molar cementation solution treated soils were substantially more resistant against rainfall-induced erosion when compared to 2 M treated soil. One of the recent studies by Clarà Saracho et al 35 investigated the in uence of tangential erosion by utilizing erosion function apparatus (EFA) and reported that treatment of soil sample with one pore volume of 0.08 M biocementation solution for 10 days brought values down to a negligible level for a tangential ow of 0 to 0.185 m/s 35 . As soil is rich in microbial diversity with approximately 10 9 -10 12 microorganisms per kilogram of soil nearby the ground surface 36 , any supplemented foreign bacteria has to compete with the native microorganisms for their survival in the new environment 29,30,37 . Hence, utilizing the indigenous microorganisms over the bio-augmentation approach for soil improvement has de nite advantages such as minimal intervention to native biodiversity and reducing the cost of bacterial transport.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations